2001
DOI: 10.1021/op010222x
|View full text |Cite
|
Sign up to set email alerts
|

Process Research and Large-Scale Synthesis of a Novel 5,6-Dihydro-(9H)-pyrazolo[3,4-c]-1,2,4-triazolo[4,3-a]pyridine PDE-IV Inhibitor

Abstract: An efficient synthesis of the PDE IV inhibitor, 9H-cyclopentyl-7-ethyl-3-(thiophen-2-yl)-pyrazolo[3,4-c]-1,2,4-triazolo-5,6-dihydro-[4,3-a]pyridine 1 is described. Starting from commercially available γ-caprolactone, the synthesis was carried out in 10 steps. Key transformations were the selective O-methylation of diketone, 3-hydroxy-1-(4-methoxybenzyl)-4-propionyl-5,6-dihydro-1H-pyridin-2-one, with dimethyl sulfate and cesium carbonate in dimethylformamide, a one-pot pyrazole formation with subsequent acidic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…In the literature (15)(16)(17), these methods often contain two steps: first, intermediates (hydrazide or hydrazone) were synthesized; then, fused 1,2,4-triazoleheterocycles were prepared via catalyst or catalyst free. The one pot cyclization reaction of hydrazide with substituted acid in POCl 3 under microwave irradiation led to novel 1,2,4-triazolo [4,3-a]pyridines.…”
Section: Synthesismentioning
confidence: 99%
“…In the literature (15)(16)(17), these methods often contain two steps: first, intermediates (hydrazide or hydrazone) were synthesized; then, fused 1,2,4-triazoleheterocycles were prepared via catalyst or catalyst free. The one pot cyclization reaction of hydrazide with substituted acid in POCl 3 under microwave irradiation led to novel 1,2,4-triazolo [4,3-a]pyridines.…”
Section: Synthesismentioning
confidence: 99%
“…Fused heterocyclic compounds often display two heterocycle functions. It has been reported that 1,2,4‐triazolo[4,3‐ a ]pyridine possesses excellent biological activities . The incorporation of a pyridine ring into the triazole ring is considered to be a good way to produce novel active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the antitumor potential of triazole conjugated pyridine has also been established in various malignancies . Some of the reports also indicated that triazolo‐pyridine conjugates target PDE4 to induce their biological effect . Specifically, synthesis of a PDE4 inhibitor, 5,6‐dihydro‐9 H ‐pyrazolo[3,4‐ c ]‐1,2,4‐triazolo[4,3‐ a ]pyridine was described .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Some of the reports also indicated that triazolo-pyridine conjugates target PDE4 to induce their biological effect. [22,23] Specifically, synthesis of a PDE4 inhibitor, 5,6-dihydro-9H-pyrazolo [3,4-c]-1,2,4-triazolo[4,3-a]pyridine was described. [23] In another study, the substitution at the 3-position of 5,6-dihydro-(9H)-pyrazolo [3,4-c]-1,2,4-triazolo [4,3-a]pyridine tricycle led to a 2-thienyl analog (Tofimilast) which is a potent PDE4 inhibitor with low oral bioavailability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation